BIOLOGY AND HOST RANGE OF THE TARO PLANTHOPPER, Tarophagus proserpina Kirk. - Duatin, Cecile Joy Y.; De Pedro, Lorenza B. (Annals of Tropical Research, 1986)
The biology of the taro planthopper was studied in the laboratory using taro as food. The total developmental periods of the male and female planthoppers are ± 30.86 days and ± 31.29 days, respectively. The insect undergoes five nymphal instars with a duration of 1.31 and 1.25 days in males and females for the first stadium to 17.58 and 17.50 days for the fifth stadium. The female hopper lives longer than the male. Both sexes are morpho-logically similar except in size and genital structures. Low percentage mortality (8%) was observed during the first to the third instar. Possible alternate hosts of taro planthoppers are ornamental gabi, Caladium bicolor (Ait) Vent.; yautia, Xanthosoma sp.; sweet potato, Ipomoea batatas (L.) Lam; cassava, Manihot esculenta Crantz; and weeds such as milkweed, Euphorbia hirta L; kangkong, Ipomoea aquatica Forsk.; gabi-gabi, Monochoria vaginalis (Burm.f.) Presl.; and alikbangon, Commelina benghalensis L. Natural enemies observed on taro planthoppers were ants, a species of predaceous mite belonging to Family Trobidiidae and a minute gastropod.